Comparative Transcriptomic Analysis Identifies Key Cellulose Synthase Genes (CESA) and Cellulose Synthase-like Genes (CSL) in Fast Growth Period of Flax Stem (Linum Usitatissimum L.) - Guo, Yuan; Wen, Lan; Chen, Jikang; Pan, Gen; Wu, Zhimin; Li, Zheng; Xiao, Qingmei; Wang, Yuanchang; Qiu, Caisheng; Long, Songhua; Zhao, Xinlin; Wang, Hui; et al. (Journal of natural fibers, 2022)
The cellulose synthase gene superfamily is vital for cell wall biogenesis during plant growth, particularly for flax fiber development. This study performed asequencing search of key CESA and CSL genes from several flax stem parts at different fiber development stages by comparing RNA-Seq. Quantitative RT-PCR was used to validate the expression of these genes. This study revealed that CESA4 genes (Lus10008225.g and Lus10008226.g), CESA6 genes (Lus10006161.g and Lus10041063.g), CESA8 genes (Lus10007296.g and Lus10029245.g), CSLD4 gene (Lus10026568.g), CSLE1 (Lus10016625.g) and CSLG genes (Lus10023056.g and Lus10023057.g) were specifically expressed in stem below the snap point where fibers is increased amounts of secondary cell wall deposition. LusCESA4 genes, LusCESA8, genes and LusCSLD4 gene were specifically expressed in fiber development stage during the fast growth period of flax plants. Based on GO and KEGG analyses, it was found that genes involved in pathways of cellulose microfibril organization, galactosyl transferase activity and galactose metabolism were specifically enriched in the stem tissue of the fiber development stage. Other genes involved in cellulose biosynthesis and cell wall development were also analyzed and discussed. The results will provide an important foundation for understanding fiber cell wall biogenesis, particularly the roles of LusCESAs and LusCSLs in the process of fiber development.